PURIFICATION OF ANGIOTENSIN CONVERTING ENZYME INHIBITORY PEPTIDE DERIVED FROM KACANG GOAT MEAT PROTEIN HYDROLYSATE - Jamhari, J.; Yusiati, L.M.; Suryanto, E.; Cahyanto, M.N.; Erwanto, Y.; Muguruma, M. (Diponegoro University, 2013)
The objective of this study was to identify the Angiotensin Converting Enzyme (ACE) inhibitorypeptide derived from Kacang goat meat protein hydrolysate. Kacang goat meat loin section washydrolyzed with pepsin, trypsin and chymotrypsin. Protein hydrolysate of Kacang goat meat was thentested the protein concentration and ACE inhibitory activity. ACE inhibitory peptide of the proteinhydrolysate was purified through several steps of purification by column SEP-PAK Plus C18 Cartridgeand RP-HPLC using a Cosmosil column 5PE-SM, 4.6 x 250 mm. The sequence of amino acid of ACEinhibitory peptide was identified by amino acid sequencer. The results showed that amino acidssequence of ACE inhibitory peptide derived from protein hydrolysate of Kacang goat meat was leu-thrglu-ala-pro-leu-asn-pro-lys-ala-arg- asn-glu-lys. It had a molecular weight (MW) of 1581 and occurredat the position of 20th to 33rd residues of b-actin of goat meat protein (Capra hircus). The ACE inhibitoryactivity (IC50) of the peptide was 190 mg/mL or 120 mM.